Invocation of State Responsibility for Violation of Obligations Owed to the International Community as a Whole - Shchokin, Yuriy (Problems of legality, 2021)
The article discusses the features of the application of paragraph 1 (b) of Art. 48 of the Draft Articles on State Responsibility, developed by the UN International Law Commission and taken into consideration by the UN General Assembly by its resolution 56/83 of December 12, 2001. The norm of this article enshrines the right of any state that is not a victim to call to international legal responsibility state that has committed a breach of an obligation owed to the international community as a whole. This rule contributes to the establishment in modern international law of the ancient Roman theory of actio popularis, according to which any citizen could file a claim in the public interest. The UN International Law Commission is considering paragraph 1 (b) of Art. 48 of the 2001 Draft Articles on State Responsibility as a result of the progressive development of International Law. This is manifested primarily in a new approach to the interpretation of concepts such as “the international community as a whole” and “obligation owed to the international community as a whole”. The article notes that the concept of "the international community as a whole" should no longer be considered as a community of sovereign states, since it already presupposes a more active participation in maintaining international legitimacy of all participants of international relations – subjects of international law. In addition, attention is drawn to the fact that the concept of “obligation owed to the international community as a whole” is a new category proposed by the International Law Commission as a part of the progressive development of the theory of erga omnes and jus cogens norms. The author compares these types of obligations and points out a number of problems that may arise while interpreting this concept in order to apply this rule in practice.